The performance of Nagrak and Kampung chicken kept intensively in Cibadak Sukabumi, West Java - Nataamijaya, Achmad Gozali (Indonesian Animal Sciences Society, 2009)
A study on the performance of Nagrak and Kampung chicken under intensive management system was conducted in Cibadak District of Sukabumi West Java. As many as 200 hens of Nagrak and Kampung, each were placed in individual cages. The birds were given 90 g of diet daily, the diet was the mixture of layer commercial diet and ricebran at equal ratio, drinking water was given ad libitum. Artificial insemination was conducted every three days using semen collected from 20 cockerels of each local bird. Disease control was done by vaccination against Newcastle Disease and Infectious Bursal Disease. Sulfamix and antibiotics were given whenever needed. Eggs were collected twice a day, weighed and stored to be incubated or to be analyzed for their characteristics. Parameters observed were physical appearance, hen-day egg production, egg quality, egg fertility and hatchability, body weight, feed conversion and mortality. Results showed that Nagrak chicken physical appearance was different from that of Kampung chicken, yet their hen-day production were not significantly different (26.93 ± 14.10% vs 27.04 ± 16.20%). The egg characteristics of these birds (Nagrak vs Kampung) were as follows: egg weight (36.29 ± 6.50 g vs 35.55 ± 5.42 g); yolk weight (16.61 ± 1.34 g vs 16.22 ± 2.11 g); albumen weight (17.31 ± 2.64 g vs 16.87 ± 1.35 g); shell weight 37 ± 0.81 g vs 2.46 ± 0.54 g); yolk color (9.62 ± 1.81 g vs 9.67 ± 1.70 g); haugh unit (83.60 ± 5.41 vs 83.45 ± 6.10); shell thickness (24.0 ± 0.83 µm vs 24.4 ± 0.67 µm), however no significant difference was found. Neither the egg fertility, hatchability nor mortality rate of the birds was significantly different. At 12 weeks old the average body weight of male Nagrak chicken (1260.04 ± 57.33 g) was much higher (P<0.01) than that of male Kampung chicken (750.68 ± 60.11 g) while the average body weight of female Nagrak chicken (980.37 ± 48.11 g) was much higher (P<0.01) than that of female Kampung chicken (656.11 ± 58.47 g). The feed conversion ratio of male Nagrak chicken (4.21) was better (P<0.05) than that of male Kampung chicken (5.62), the feed conversion ratio of female Nagrak chicken (5.15) was also better (P<0.05) than that of female Kampung chicken (6.81). No significant difference was found on the feed conversion ratio of Nagrak hens (9.24) and Kampung hens (9.06). Key words: Performance, Nagrak, Kampung, Local Chicken